Analisis Faktor-Faktor Pengambilan Keputusan Masyarakat Dalam Memilih Jasa Pelayanan Kesehatan Di Rumah Sakit Umum Daerah (RSUD) Dr. Mohammad Soewandhie Kota Surabaya - Ricke Zeyna Virnata; Ananda Diane Masayu (Journal of Research and Development on Public Policy, 2024)
Patient satisfaction is a competitive advantage for every hospital to retain its customers and enable the hospital to continue to compete and grow every day. This study examines patient satisfaction as a significant competitive advantage for hospitals, focusing on Dr. Mohamad Soewandhie Hospital in Surabaya. This study uses qualitative descriptive method with literature review approach to assess the quality of hospital services based on five main indicators: physical evidence (tangibles), reliability, responsiveness, empathy, and assurance. This study concluded that the quality of service at Dr. Mohamad Soewandhie Hospital has met these indicators, so as to increase patient satisfaction and compete in the health industry.